IMPLEMENTASI KEBIJAKAN PEMANFAATAN BANK SAMPAH INDUK (BSI) KUMALA DI KELURAHAN SUNGAI BAMBUKECAMATAN TANJUNG PRIOK JAKARTA UTARA - Deni Nurdin; Sisman Prasetyo; Angella Rosha Pangestu (Department of Public Administration, Faculty of Social and Political Science, Universitas, 2025)
This research is designed to explore the Policy Implementation concerning the Utilization of BSI Kumala in Sungai Bambu Village, Tanjung Priok District, North Jakarta. This study applies a qualitative methodology with a descriptive approach, where data was collected through structured interviews, observation, and documentation. Furthermore, the data analysis technique included the stages of Data Collection, Data Reduction, Data Display, and Conclusion Drawing/Verification, while the validity of the findings was tested using source triangulation directly in the field. This study adopts the theoretical framework proposed by George C. Edward III (in Subarno, 2021), namely the theory of public policy implementation, to determine the implementation of the policy on the utilization of BSI Kumala in Sungai Bambu Village and to evaluate whether the regulation has been implemented effectively. The results of this research indicate that out of the three indicators applied, communication, disposition, and organizational structure have been functioning as intended, although they have not yet reached their maximum potential. Meanwhile, one other indicator, the number of available personnel, is not yet adequate, and there is a need for additional workforce from the BSI Kumala management in Sungai Bambu Village, Tanjung Priok District, North Jakarta